Clinical and histopathological effects of presurgical treatment with sunitinib for renal cell carcinoma with inferior vena cava tumor thrombus at a single institution. Issue 10 (November 2016) - Ujike, Takeshi; Uemura, Motohide; Kawashima, Atsunari; Nagahara, Akira; Fujita, Kazutoshi; Miyagawa, Yasushi; Nonomura, Norio
Abstract : To evaluate the clinical and histopathological effects of presurgical treatment with sunitinib on inferior vena cava (IVC) tumor thrombus. Between 2010 and 2014, we treated seven patients with renal cell carcinoma and IVC tumor thrombus presurgically with sunitinib. We retrospectively evaluated primitive tumor size, the level of tumor thrombus according to Novick's classification, its distance above the renal vein, thrombus diameter at its widest segment, and histopathological change after sunitinib treatment. Three patients were diagnosed histologically. Percutaneous biopsy of the renal mass before sunitinib treatment was performed in two patients. One patient was diagnosed after sunitinib treatment following nephrectomy. The primitive tumors shrank upon sunitinib therapy in four cases; however, although the caval thrombus was downstaged (from level II to I) in one patient, the level of caval thrombus did not change in five patients and increased in one patient (from level III to IV). We evaluated the histopathological effects in two patients. In one patient, the IVC tumor thrombus was mostly replaced with necrotic tissue, but its thrombus level was not downstaged. In the other patient, the IVC tumor thrombus was downstaged, but tumor thrombus was not replaced with necrotic tissue and viable tumor cells remained. Presurgical treatment with sunitinib for renal cell carcinoma with IVC tumor thrombus appears to have limited effect on IVC tumor thrombus, in contrast to its effects on primitive tumor shrinkage. In the absence of evidence of presurgical benefits from prospective studies, this treatment may not be systematically advisable.